Sustainable Food Security: Floating Balance of Markets - Kuzmin, Evgeny A. (International Journal of Economics and Financial Issues, 2016)
The paper deals with pressing issues in food security. The research focus is on defined specifics of a price factors' influence on a balance in a market. The paper specifies features of food security and there is a conclusion of its division into static and dynamic. The subsequent development of ideas on dynamic security has led to a defined “floating” balance, when the market due to its movement inertia crosses an equilibrium point, from a condition of relative deficit to an account surplus of supply and demand, and vice versa. With an analytical review of known scientific approaches, in the paper, there is an assumption that any national food market is more subject to price volatility than the global market. These and other features have allowed finding a number of sustainable regularities in an influence of changes to prices upon a status of security. Keywords: food security; price factors; market equilibrium and balance; risks; uncertainty; self-organization JEL Classifications: Q01; Q11; Q17